Endoscopic Drainage of Pancreatic Pseudocysts: An Experience with 77 Patients - Hemanta K. Nayak; Sandeep Kumar; Uday C. Ghoshal; Samir Mohindra; Namita Mohindra; Gaurav Pande; Vivek Anand Saraswat (Journal of Digestive Endoscopy, 2017)
Background: We evaluated short‑ and long‑term results of endoscopic drainage (a minimally invasive nonsurgical treatment) of pancreatic pseudocysts (PPCs) and factors associated with its success at a multilevel teaching hospital in Northern India, as such data are scanty from India. Patients and Methods: Retrospective review of records of consecutive patients undergoing endoscopic drainage of PPC from January 2002 to June 2013 was undertaken. Results: Seventy‑seven patients (56 males), median age 36 years (range, 15–73), underwent endoscopic drainage of PPC with 98% technical success. Pseudocysts drained were symptomatic (duration 11 weeks, range, 8–68), large (volume 582 mL [range, 80–2706]), located in head (n = 32, 46%), body and tail (n = 37, 54%), and infected (n = 39, 49%). Drainage procedures included cystogastrostomy (n = 54, 78%), cystoduodenostomy (n = 9, 13%), transpapillary drainage (n = 2, 3%), and multiple route (n = 4, 6%), with additional endoscopic nasocystic drainage (ENCD) in 41 (59%). Sixty‑nine patients were followed up (median 28 months, range 2–156; other eight lost to follow‑up). Complications (n = 21, 30%) included stent occlusion and migration (13), bleeding (5), perforation (2), and death (1). Endoscopic procedure had to be repeated in 19 patients (28%; 16 for sepsis, 3 for recurrence). The reasons for additional nonendoscopic treatment (n = 8, 12%) included incomplete cyst resolution (3), recurrence (2), bleeding (1), and perforation (2). Overall success rate of endoscopic drainage was 88%. Whereas infected pseudocysts were associated with poorer outcome (odds ratio [OR] 0.016; 95% confidence interval [CI] 0.001–0.037), placement of ENCD led to better results (OR 11.85; 95% CI 1.03–135.95). Conclusion: Endoscopic drainage is safe and effective for PPC.